White Clover: SS-AGR-54/AA198, rev. 6/2020 - Dubeux, Jose; Blount, A. R.; Rios, Esteban (EDIS, 2020)
The document provides information on white clover, a cool-season legume that acts like an annual in Florida. It discusses the superior feed value of white clover-grass mixtures, recommended varieties, establishment practices, management recommendations for grazing, irrigation, reseeding, summer live-over, and fall regrowth. The document also addresses factors affecting white clover growth, such as nematodes, viral diseases, drainage ditches, and irrigation availability. It emphasizes careful site selection for successful white clover cultivation.